Chinese "taukeh", labourer, and state control; Case study of "panglong" in eastern region of Sumatra (1890-1930) - Erman, Erwiza (Wacana, Journal of the Humanities of Indonesia, 2017)
Recently the flow of labour from China to Indonesia has fuelled many discussions but is not a new phenomenon. It can be traced back to the eighteenth century and continued until the twentieth century. In colonial Indonesia, the Chinese labour force was recruited to work in the economic sectors of mining, plantations, fisheries and forestry. Unfortunately, previous studies about Chinese society in Indonesia more focused on economic and political elites rather than the social history of the Chinese contract coolies. This article attempts to look at the labour history of the Chinese coolie in the forest exploitation companies, known as panglong. By focusing on the ways in which they were treated in the recruitment process and workplace, this article shows that changes for the better did take place in the appalling working conditions of the labourers. Until the second decade of the twentieth century, recruitment, food, and health care were rife with manipulations, exacerbated by arduous working conditions and insecurity in the workplace, abuse of power by mandors and forms of non-economic coercion like the use of opium. All these factors were meant to ensure that the Chinese contract labourers could not break loose from their indentures, a modern form of slavery. Hampered by budgetary restrictions, lack of personnel, and marine transport facilities, the state colonial officials were hamstrung. But in the second decade of twentieth century, when the abysmal working conditions of the Chinese coolies were debated on a higher level by politicians and bureauracts state control was tightened. More effectual control by the state had a positive effect on improving of the working and living conditions.